Effect of Rotor Teeth Width Variations on Back EMF Constant of a 12-Slot 8-Pole Permanent Magnet Synchronous Generator: A Finite Element Analysis - Darmawan, Isra' Nuur; Mudilulail, Sahid Aktob; Kholistianingsih, Kholistianingsih (MSD Institute, 2024)
Permanent Magnet Synchronous Generators (PMSGs) are widely used for converting mechanical energy into electrical energy through electromagnetic induction. Unlike conventional generators, PMSGs utilise permanent magnets to generate the excitation field, eliminating the need for external excitation coils. This study investigates the effects of rotor teeth width variations on the performance characteristics of a 12-slot, 8-pole PMSG using Finite Element Method (FEM) simulations. Specifically, the influence of rotor teeth width on flux density and back electromotive force (EMF) constant are explored. Three different rotor teeth widths, 5 mm, 7.5 mm, and 10 mm, are considered, and their impact on the generator's performance is evaluated. The FEM simulations reveal that increasing the rotor teeth width leads to a significant increase in the back-EMF constant values. The smallest back-EMF of 12.057 V and the lowest constant are observed for the 5 mm rotor teeth width, while the largest back-EMF of 20.774 V and the highest constant correspond to the 10 mm rotor teeth width. These findings highlight the importance of optimising rotor teeth geometry in PMSGs to achieve desired performance characteristics.